An ethical evaluation of philanthropic strategies employed by charitable organisations operating in Mongu district of Western Zambia - Mutemwa, David (Jihočeská univerzita, 2023)
This study has been prompted by the fact that very little is known about the ethical aspects and operating strategies of charitable organisations in Mongu district of Western Zambia despite an influx of such organisations in the area from pre-colonial times. The aim of the study is to evaluate the ethical aspects of philanthropic strategies employed by charitable organisations operating in Mongu. Within social work, which is the guiding framework of this study, evidence of results alone does not satisfy the ethical aspect because ethics in social work are mainly deontological in nature, which means that the end does not always justify the means. The study endeavours to contribute to the discourse of philanthropic social work and, especially, towards a model for evaluating ethical aspects of philanthropic strategies of charities from the unique context of the charitable organisations operating in Mongu district of Western Zambia, which will also inform praxis in other similar contexts.
An ethical evaluation of philanthropic strategies employed by charitable organisations operating in Mongu district of Western Zambia
An evaluation of ethical aspects of philanthropic strategies employed by charitable organisations operating in Mongu district of Western Zambia
Keywords: ethics; philanthropy; strategies; charitable organisations (NGO/s); Mongu; Zambia; ethics; philanthropy; strategies; charitable organisations (NGO/s); Mongu; Zambia